Long-term Patient Perception Following Surgery for Adolescent Idiopathic Scoliosis if Dissatisfied at 2-year Follow-up. Issue 8 (15th April 2021) - Hughes, Jessica; Yaszay, Burt; Bastrom, Tracey P.; Bartley, Carrie E.; Parent, Stefan; Cahill, Patrick J.; Lonner, Baron; Shah, Suken A.; Samdani, Amer; Newton, Peter O.
Abstract : Study Design: Longitudinal. Objectives: To evaluate whether the rate of patients who report low health-related quality of life (HRQOL) scores at 2 years following surgical correction of adolescent idiopathic scoliosis (AIS) improves by 5 years postoperatively. Summary of Background Data: HRQOL scores are dependent upon a number of factors and even in instances of good surgical correction of a spinal deformity, are not guaranteed to be high postoperatively. Understanding how a low HRQOL score varies over the postoperative period can help surgeons more effectively counsel patients and temper expectations. Methods: A multicenter database was reviewed for patients with both 2 and 5-year follow-up after spinal fusion and instrumentation for AIS. From a cohort of 916 patients, 52 patients with low HRQOL scores at their 2-year follow-up were identified and reevaluated at 5-year follow-up. A low HRQOL outcome was defined as having SRS-22 domain or total scores less than 2 standard deviations below the mean score. Reoperations were also evaluated to determine if they were associated with HRQOL scores. Results: Of those patients with low SRS-22 HRQOL scores at 2 years postoperatively, improvements were seen in all SRS-22 domains and total scores at the 5-year time point. The greatest change was seen in the satisfaction category where 41 patients showed improvement. The rate of reoperations during this period did not significantly impact patient-reported outcomes. Conclusions: Having a low HRQOL score 2 years after surgery for AIS does not guarantee a low score 5 years after surgery. Promisingly, most patients demonstrate some improvement in all domains for patient-reported SRS-22 scores at 5-year compared to 2-year follow-up. Understanding the longer term postoperative evolution in patient-reported outcomes may help surgeons to effectively manage and counsel patients who are dissatisfied in the short term. Level of Evidence: 3 Abstract : Among AIS patients with low HRQOL scores 2 years postoperatively, there were fewer patients with low HRQOL scores at 5 years than at 2 years in all SRS-22 domains, suggesting a perceived improvement with time and a role for optimism and patience if expectations are not met at 2 years.